2015
DOI: 10.1089/g4h.2014.0101
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cost and Enjoyment of Active Videogames in Children and Teens: Xbox 360 Kinect

Abstract: AVGs elicited sufficient energy cost to be a suitable alternative for traditional play and may contribute to the recommended dose of physical activity, particularly in teens, males, and overweight youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
15
0
4
Order By: Relevance
“…Previous studies have reported that a single AVG session induces a significant increase in HR, SBP, DBP, and hence in DP [1,2,4,5,23]. However, the PEH phenomenon in relation to AVG remains unclear.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have reported that a single AVG session induces a significant increase in HR, SBP, DBP, and hence in DP [1,2,4,5,23]. However, the PEH phenomenon in relation to AVG remains unclear.…”
Section: Resultsmentioning
confidence: 96%
“…on the other hand, active video games (AVG), in which the players have to remain physically active to succeed during matches, help to improve fitness levels and to develop motivation for physical activity [1,2]. Several studies with AVG have been carried out in order to verify the improvement of energy expenditure, aerobic capacity, and body composition [2][3][4]. AVG turn out a practical and attractive way to change sedentary behaviours in different populations [2].…”
Section: Introductionmentioning
confidence: 99%
“…The 4 active video games (Kinect Adventures Reflex Ridge, Just Dance 3, Wipeout, and Kinect Sports Boxing) were chosen because they had produced at least moderate-level physical activity in prior literature. 5,8 The 2 games chosen, the order in which the games were played, and the order in which the participants played single-or multiplayer were randomly decided. If the player completed a level within the 15-minute period s/he was instructed to begin the next most basic level.…”
Section: Methodsmentioning
confidence: 99%
“…Research showed that AVGs can significantly increase energy expenditure (EE) and physical activity compared to sedentary video games (Graves, et al, 2010), proving to be a suitable alternative to traditional play or moderate-intensity physical activity in teen (Clevenger & Howe, 2015) and young men (Barry, et al, 2016). Considering the popularity of Zumba ® Classes (ZC) among fitness activities (Thompson, 2011(Thompson, , 2012 (Barry, et al, 2016;Graves, et al, 2010), researchers (Ainsworth, et al, 2011;Barry, et al, 2016;Graves, et al, 2010) (ACSM, 2014).…”
Section: Introductionmentioning
confidence: 99%